Proposta de metodologia de requisitos para a inovação em micro e pequenas empresas - Serpe, Luís Filippe (2014)
The development of organizations, due to an increasing competitive environment, faces challenges which grow in an accelerated rate. Thus, the technological innovation appears as an important instrument in the maintenance of a competitive scenario inthe organizations. When analysing the question, it can be observed that there are many tools tohelp obtaining the innovation indexes. However, the focal point is that companies be capable of developing innovation in a continuous and sustainable way, towards the increase in their innovative activities and the improvement of their competitive performance. It can also be observed that the micro enterprises show the major difficulties concerning the development of such process, due to many factors. Thus, the central objective of this study is to propose a methodology of solutions and requisites, aiming to increase the innovation degree in micro and small enterprises. The data collection is represented by the diagnosis, observing the degree of innovation within the researched companies, obeying to specific criteria, which also served as a parameter to the execution of the main objective. The proposition of the model shows some degrees of commitment of the organizations, concerning the innovation activities described. In other words, it identifies in which level the companies are located. (Looking for ideas, Selection of ideas, Gathering of resources; Execution). To facilitate the data collection, the activities were divided in six (6) dimensions. Such activities were formulated following parameters described by the Oslo Manual –Guidelines for Collecting and Interpreting Innovation Data, and the researched literature. Through the use of tables and figures indicating the localization of the companies in each dimension, it is possible to identify which items must be improved within the four (4) activity levels, then offering the proposition of requisites. The results showed that the researched companies have medium levels of evolution concerning the described activities, highlighting the lack of understanding on the importance of the activities. Notwithstanding, it was possible to operationalize the proposition, showing how the phases are applied.